Educação e cultura empreendedora: a preparação do corpo docente de uma instituição de ensino profissionalizante no Estado de São Paulo (2009)
This article refers to the development of a methodology for teacher training with the purpose of expanding entrepreneurial culture in vocational schools. Educational references and theoretical bases for the development of teachers’ pedagogical skills, as well as the core subjects for teacher training have been defined based on the construction of the concept of “Entrepreneurial Attitude”. The pedagogic structure of the Entrepreneurial Culture Educational Development Program was based on meaningful learning (Ausubel). The (pedagogic) project is based on the Theory of Roles (J. L. Moreno) and on the Social Cognitive Theory (A. Bandura). The approach of subjects related to entrepreneurism has the purpose of developing Entrepreneurial Education by changing the attitude in the institution’s teaching-learning process. In this text, we present the general assessment of teachers that took part in the training in 2007 concerning the program and the proposal for creating educational techniques for developing an entrepreneurial attitude in vocational schools.